Measuring What Matters: Extended-Cosmic Functional Points as a Foundation for Government Software Cost Estimation - Ratih Indhi Dewastri; Sholiq Sholiq (International Journal Labs, 2026)
The East Java Provincial Government has established standards for application development through Governor Regulation No. 98 of 2018; however, it lacks a standardized method for estimating development costs based on system complexity. This discrepancy leads to significant budget variations across regional agencies, impacting consistency, transparency, and accountability in budgeting. This study proposes an extended method for cost estimation using Extended-COSMIC Function Points (FP), aimed at providing a reliable and measurable basis for government application development. System complexity is first assessed using COSMIC FP, followed by the conversion of the functional size into estimated effort, which is then translated into cost estimates according to the pay rates stipulated in the Decree of the Minister of Communication and Information Technology No. 117 of 2024. The method was tested on 15 applications, yielding a Mean Relative Error (MRE) of 12.30% and a Predictive Accuracy (PRED) of 93.33%. The results demonstrate that the Extended-COSMIC FP method provides accurate, consistent, and transparent cost estimates, ensuring more reliable budget planning in government application projects. The method's high accuracy and practical applicability make it a valuable tool for standardizing cost estimation across governmental IT projects